DEVELOPMENT OF NEWS WRITING LEARNING MODULE BASED ON CONTEXTUAL APPROACH FOR STUDENTS OF PBSI - Agus Wismanto (Universitas PGRI Semarang, 2021)
This research was conducted to describe the process of developing a news writing learning module based on a valid, practical, and effective contextual approach for students of PBSI (Indonesian Language and Literature Education). This type of research is development research (R&D). The development model used is 4-D (definition, design, development, and deployment). This research was conducted at the Indonesian Language and Literature Education Study Program, Faculty of Language and Arts Education, Universitas of PGRI Semarang with a total of 30 students. This development process produces a product in the form of a news writing learning module based on a valid, practical and effective contextual approach. The overall module validity value is 85.36% with a very valid category. Practical scores were obtained in three ways, 86.22 % from lecturers in the very practical category, 93.12% from students in the very practical category, and 88.59% in student activity assessments in the very practical category. The assessment of the effectiveness of the module was obtained through a pretest and posttest design. Based on data analysis, it is known that the news writing learning module based on a practical and effective contextual approach is used in improving the ability to write news in PBSI Study Program students..Keywords: learning module, news writing, contextual approach